2-Hydroxymethyl-3,4-dihydroxy-6-methyl-pyrrolidine (6-deoxy-DMDP), an alkaloid beta-mannosidase inhibitor from seeds of Angylocalyx pynaertii. - Molyneux, R; Pan, Y; Tropea, J; Elbein, A; Lawyer, C; Hughes, D; Fleet, G (1993)
A polyhydroxy alkaloid has been isolated from the seeds of the African legume Angylocalyx pynaertii and identified as a 2-hydroxymethyl-3,4-dihydroxy-5-methylpyrrolidine by ms and 1H- and 13C-nmr spectroscopy. The absolute stereochemistry was established, by a stereochemically unambiguous synthesis from diacetone glucose, as 2,5-imino-1,2,5-trideoxy-D-mannitol, which may also be regarded as 2R,5R-dihydroxymethyl-3R,4R-dihydroxypyrrolidine (DMDP) [2] in which a hydroxymethyl group is deoxygenated, i.e., 6-deoxy-DMDP [1]. Whereas the structurally related polyhydroxypyrrolidine alkaloids which have previously been discovered are inhibitors of alpha- and beta-glucosidase, 6-deoxy-DMDP is unique in inhibiting beta-mannosidase. In addition to this novel alkaloid and 2-hydroxymethyl-3,4-dihydroxypyrrolidine [3], previously shown to be present in several Angylocalyx species, the known piperidine alkaloids deoxymannojirimycin [4] and fagomine [5] were identified for the first time as constituents of An. pynaertii seeds.